Horseradish peroxidase catalyzed grafting of chitosan oligosaccharide with different flavonols: structures, antioxidant activity and edible coating application. (7th February 2022) - Yong, Huimin; Hu, Huixia; Yun, Dawei; Jin, Changhai; Liu, Jun
Abstract: BACKGROUND: Enzymatic catalyzed grafting of oligosaccharides with polyphenols is a safe and environmentally friendly approach to simultaneously enhance the bioactivity of oligosaccharides and the solubility of polyphenols. In this study, chitosan oligosaccharide (COS) was grafted with three different flavonols including myricetin (MYR), quercetin (QUE) and kaempferol (KAE) by horseradish peroxidase (HRP) catalysis. The structures, antioxidant activity and edible coating application of COS–flavonol conjugates were investigated. RESULTS: The total phenol content of COS–MYR, COS–QUE and COS–KAE conjugates was 59.89, 68.37 and 53.77 mg gallic acid equivalents g −1, respectively. Thin layer chromatography showed the conjugates did not contain ungrafted flavonols. COS–flavonol conjugates showed ultraviolet absorption peak at about 294 nm, corresponding to the A‐ring of flavonols. Fourier‐transform infrared spectra of conjugates confirmed the formation of Schiff‐base and Michael‐addition products. The proton‐nuclear magnetic resonance spectrum of COS–KAE conjugate exhibited phenyl proton signals of KAE. X‐ray diffraction patterns of conjugates showed some diffraction peaks of flavonols. COS–flavonol conjugates presented rough and porous morphologies with sheet‐like and/or blocky structures. The conjugates showed higher water solubility, free radical scavenging activity and reducing power than flavonols. Moreover, fish gelatin/COS–flavonol conjugate coatings effectively prolonged the shelf life of refrigerated largemouth bass ( Micropterus salmoides ) fillets from 5 days to 7–8 days. CONCLUSION: COS–flavonol conjugates prepared by HRP catalysis have great potentials as novel antioxidant agents. © 2022 Society of Chemical Industry. Abstract : Chitosan oligosaccharide (COS) was grafted with three different flavonols including myricetin, quercetin and kaempferol by horseradish peroxidase catalysis. The obtainedCOS‐flavonol conjugates showed higher water solubility, free radical scavenging activity and reducing power than flavonols. Moreover, fish gelatin/COS‐flavonol conjugate coatings effectively prolonged the shelf life of refrigerated large mouth bass (Micropterus salmoides) fillets from 5 days to 7–8 days.